Learning from Errors and Mishaps: An Audit of Hospital Morbidity Events from a Medical Oncology Unit - Sandhya, Singuluri; Nisha, Yadav; Pichai, Sunantha; Priyanka, Narayanan; Sarvanapriya, Murugaiyan; Kayal, Smita; Ganesan, Prasanth; Dubashi, Biswajit (Indian Journal of Medical and Paediatric Oncology, 2025)
Morbidity, an unwanted and often preventable event, is an integral part of cancer treatment. Various morbidity events can contribute to significant toxicities and delay treatment. We intend to describe a novel morbidity data collection methodology to identify all possible morbidity events, learn from mishaps, and improve internal standards to prevent future occurrences.This article aims to understand the various morbidity events occurring during chemotherapy among patients undergoing treatment in the medical oncology unit.Data were collected from January 2019 to March 2020 from the department of medical oncology of a tertiary cancer center. The treating team notified the morbidity events via a closed WhatsApp group. These events were prospectively recorded by a nurse who updated various events from all work areas in a defined Excel sheet.A total of 2,551 patients were registered for treatment from January 2019 to March 2020. A total of 864 morbidity events were recorded: 423 (48%) catheter-related events, 54 (6%) medical errors, 45 (5%) transfusion reactions, 210 (25%) miscellaneous morbidity events, and 31 (3%) unknown events. The median age was 26 years (1–70), with the majority of the events seen among adolescent young adult patients, 422 (48.9%). Catheter-related events were found in the majority, with central line–associated bloodstream infection being one of the significant causes of morbidity and catheter removal (13.3%). Hence, a catheter maintenance team was introduced. Catheter maintenance was successful in 36.8% (117/426).A structured, uniform, and prospective record of the morbidity events during treatment is essential to understanding errors, which can provide an opportunity to rectify future events. The periodic audit of events can help in establishing standardized operating procedures to minimize error and maximize safety.Morbidity event definitions and recognition plus reporting are essential to understand and prevent future events.
Keywords: morbidity; chemotherapy-related toxicity; central line-associated bloodstream infection; transfusion reaction